Representing organization - Lilley, Simon (Oxford University Press, 2004)
An accessible theoretical analysis of the organizational impact of information technologies. This book examines the many ways in which actors, organizations and technologies are represented through these technologies thus bridging the gap between the abstractions of current theories of organization and the somewhat excessively grounded material on information systems